Growth of Cymbidium bicolor Lindl. plantlet during subculture with variation of media - Pratama, Fakhri Fadhlurrohman; Setiari, Nintya; Nurchayati, Yulita (Jurnal Biologi Udayana; Vol 25 No 1 (2021): JURNAL BIOLOGI UDAYANA, 2021)
Cymbidium bicolor is one of the orchids in Indonesia which has beautiful and longlasting flowers, so it has potential to become an ornamental plant and has economic value. The method of propagation generally is tissue culture. One of the stages in plant tissue culture is subculture. The variation of media used at the subculture stage make an effect for growth of plantlet. Media usually can be used include Murashige and Skoog (MS), Vacin and Went (VW), and New Phalaenopsis (NP). This study aims is to analyze the variation of media during the subculture. The method used was tissue culture in subculture with media as treatment. Cymbidium bicolor planlets were subcultured into MS, VW, and NP and observed for 2 months. The parameters observed were the leaf emergence, the number of leafs, leaf length, leaf width, the number of roots, root length, and the number of shoots. This study used a completely randomized design with single factor and 15 replicates. Data were analyzed by ANOVA with 95% significance. Treatment of variation of media significantly affected all parameters. Murashige and Skoog (MS) medium was the best medium for leaf emergence (11 days), the number of leafs (4,92), leaf length (1,56 cm), leaf width (0,33 cm), the number of roots (2,67), root length (2,73 cm), and the number of shoots (4,00). Murashige and Skoog (MS) medium was the best medium and concentrations for C. bicolor growth at the subculture stage.